Transcriptomic Analysis of Tambaqui (Colossoma macropomum) Exposed to Trichlorfon-Induced Toxicity - Hallana Cristina Menezes da Silva; Igor Kelvyn Cavalcante Lobo; André Gentil da Silva; Ana Lúcia Silva Gomes; Wallice Paxiúba Duncan; Juliana Costa Silva; Fabrício M. Lopes; Roberto Ferreira Artoni; Daniele Aparecida Matoso (Animals, 2025)
Trichlorfon is an antiparasitic agent widely used to control pests and parasites in farmed fish. Tambaqui (C. macropomum) is the most commercially important characid species farmed in the Amazon region. Trichlorfon exposure is known to cause physiological damage in fish due to its organophosphate nature. In this study, we used RNA-Seq to investigate the hepatic response of tambaqui following exposure to 0.435 mg/L of trichlorfon. The analysis revealed activation of several metabolic pathways, particularly those related to tumor processes, immune responses, and apoptosis. Additionally, we identified upregulation of solute carrier (SLC) genes, which may facilitate trichlorfon entry into hepatocytes. These findings enhance our understanding of fish responses to antiparasitic agents and support further research into the molecular impacts of organophosphate compounds in aquaculture species.